Perfil sociodemográfico de los padres y el incumplimiento de la pensión alimenticia en Iquitos 2024 - Morillas Silva, Oscar Dean (2025)
This research analyzed the relationship between the sociodemographic profile of fathers and non-compliance with child support payments in Iquitos during 2024. With a quantitative approach, descriptive-correlational level, and non experimental design, a judicial record review sheet and a questionnaire were administered to a sample of 80 fathers. The study assessed the demographic, economic, and social dimensions of the fathers' profile, as well as the economic, social, and psychological barriers associated with non-compliance. The results showed no significant correlation between the general sociodemographic profile and non-compliance (Rho =.120; p =.290), but a significant negative correlation was found between the economic dimension and non-compliance (Rho = -.257; p =.021). 80% of the fathers presented a "Moderate" profile, and paradoxically, 55% were classified with "High economic capacity," while 53.8% were placed at a "Low" level of non compliance. These findings indicate that while the general profile is not a predictor, economic capacity does play an inverse role in non-compliance, supporting the need for interventions focused on resource management rather than precarity, while also considering a possible social desirability bias in the self-reported data.